Effects of terlipressin and naloxone compared with epinephrine in a rat model of asphyxia-induced cardiac arrest (Clinics, 2013)
OBJECTIVE: To evaluate the hemodynamic and metabolic effects of terlipressin and naloxone in cardiac arrest. METHODS: Cardiac arrest in rats was induced by asphyxia and maintained for 3.5 minutes. Animals were then resuscitated and randomized into one of six groups: placebo (n = 7), epinephrine (0.02 mg/kg; n = 7), naloxone (1 mg/kg; n = 7) or terlipressin, of which three different doses were tested: 50 µg/kg (TP50; n = 7), 100 µg/kg (TP100; n = 7) and 150 µg/kg (TP150; n = 7). Hemodynamic variables were measured at baseline and at 10 (T10), 20 (T20), 30 (T30), 45 (T45) and 60 (T60) minutes after cardiac arrest. Arterial blood samples were collected at T10, T30 and T60. RESULTS: The mean arterial pressure values in the TP50 group were higher than those in the epinephrine group at T10 (165 vs. 112 mmHg), T20 (160 vs. 82 mmHg), T30 (143 vs. 66 mmHg), T45 (119 vs. 67 mmHg) and T60 (96 vs. 66.8 mmHg). The blood lactate level was lower in the naloxone group than in the epinephrine group at T10 (5.15 vs. 10.5 mmol/L), T30 (2.57 vs. 5.24 mmol/L) and T60 (2.1 vs. 4.1 mmol/L). CONCLUSIONS: In this rat model of asphyxia-induced cardiac arrest, terlipressin and naloxone were effective vasopressors in cardiopulmonary resuscitation and presented better metabolic profiles than epinephrine. Terlipressin provided better hemodynamic stability than epinephrine.